Detection of Maize stripe virus in different parts of sorghum plant and seed by penicillinase based direct antigen-coated enzyme-linked immunosorbent assay - V, MUNIYAPPA*, YO, NARAYANA and (Indian Phytopathology, 2003)
For the detection of Maize stripe virus (MStV) in different of parts of Sorghum bieolor plant and seed development stages, penicillinase based direct antigen-coated enzyme-linked immunosorbant assay (DAC-ELlSA) was used. The virus was detected in all parts including inflorescence, internodes, roots and basal tillers. The virus was detected in inflorescence to seed maturity and the percentage of detection was less in matured and dried seeds. The seedlings raised from seeds collected from MStV infected plants did not express visible symptoms in grow out test and the virus was not detected by ELISA, indicating the absence of virus transmission through seeds. The technique is of great significance in detection of viruses in seed/vegetative propagative and root materials of graminaceous hosts and also epidemiological aspects of disease.